EFEKTIVITAS PENGGUNAAN MEDIA POWER POINT (PPT) HYPERLINK DENGAN MODEL PEMBELAJARAN THINK, PAIR AND SHARE (TPS) DALAM MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA - Pratama, zakhi Restu; Isnaini, Isnaini; Aisya, Feity (Program Studi Pendidikan IPA FKIP Universitas Jember, 2024)
Abstract Education in Indonesia, as outlined in the “Republic of Indonesia Law Number 20 of 2003 concerning the National Education System, emphasizes conscious and planned efforts to create a conducive learning environment for learners to actively develop their potential”. This article discusses the need for changes in the learning process, including methods, models, strategies, and learning media, to achieve better educational quality. The current technological advancements have triggered changes in the learning system, requiring teachers to integrate technology and information into teaching. the research was conducted at SMP N 20 Bengkulu City in November 2023. Observations revealed a lack of school facilities, especially projector tools such as infocus, and the use of conventional learning models. This resulted in boredom and the ineffectiveness of teaching and learning activities. Therefore, this research proposes a solution by integrating interactive learning media, such as PowerPoint hyperlinks, and the Think, Pair, and Share (TPS) learning model. The research findings indicate that the use of PowerPoint hyperlink media and the TPS learning model is effective in improving the science process skills of junior high school students. Statistical analysis reveals a significant improvement between the pre-test and post-test. Descriptive tests, normality tests, and homogeneity tests provide an in-depth overview of the sample characteristics and data distribution. Regression analysis indicates that the applied learning model and media contribute to a 64.1% increase in students' science process skills. In conclusion, the research results show that the use of PowerPoint hyperlink media and the TPS learning model can enhance the science process skills of junior high school students. This research makes a new contribution by combining these two variables, opening up space for innovation in learning, and providing a more interactive and engaging approach for both students and teachers. Keywords: Powerpoint, TPS , Science Process Skills